Knowledge Factors and Their Impact on the Organisation (Journal of Universal Excellence, 2026)
Research Question (RQ): The research question is whether managers in organisations recognize the benefits of knowledge management.Purpose: The purpose of this research is to identify the factors of knowledge which have a significant impact on the organisation.Method: We reviewed the relevant literature in the field of knowledge management. On this basis, we summarized the factors of knowledge. We performed a survey among the 69 biggest Slovenian commercial companies (public and banking sectors were excluded). Results: Research has shown that managers recognize the positive effects of knowledge. Factor analysis, with the discovery of latent variables, additionally confirmed already established facts from the research literature. This led us to the discovery that knowledge is the common denominator of all companies, regardless of the business in which they operate. Organisation: From the examined literature, we can conclude that knowledge management has a positive impact on the company's results. Identification of knowledge factors allows a more efficient use of company’s resources and enables further development of the organisation.Society: Knowledge has become a highly appreciated "resource", therefore it is necessary to be able to manage it. Knowledge is the foundation of progress, not only for the development of the company but for the entire civilization.Originality: We see the original contribution in the identification of dilemmas in building connections between knowledge management and the company's success.Limitations / further research: The research matter is extremely difficult because the evidence that knowledge is the most influencing matter of a company’s success can not be easily confirmed. The connection (we remain inside the topic of human capital) between knowledge and company's result is also manifested with other elements of the business, such as organisational culture, public relations, etc. Additional question is whether all employees in companies have the same opinion about knowledge management, namely most of the responses to our survey were received from people who are managers, directors, etc.
Keywords: knowledge management; knowledge factors; human capital